Effect of the African Growth and Opportunity Act on the Structure of Public Revenue in Sub-Saharan Africa - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2025)
The present analysis investigates the effect of the eligibility to the African Growth and Opportunity (AGOA) programme, and of the suspension of the benefits associated with this programme on the total public revenue and its structure in beneficiary (or suspended) Sub-Saharan African countries. The analysis has shown that the eligibility to the AGOA programme has yet contributed to the increase in total public revenue, but this reflects essentially an increase in resource-based revenue. The analysis has also revealed that export product diversification and an increase in the share of manufactured exports in total merchandise exports mediate the effect of the AGOA programme on public revenue indicators in beneficiary countries. In particular, countries that diversify their export product baskets, and those that improve their manufactured export performance tend to enjoy a higher non-resource based public revenues. Finally, the suspension of the benefits from the AGOA programme leads to a decrease in total public revenue, including resource revenue and, both tax revenue (notably resource tax revenue) and nontax revenue (both the resource and non-resource components of the latter). The analysis, therefore, shows that non-reciprocal trade preferences (here, the AGOA programme) can enhance non-resource-based public revenue in beneficiary countries that endeavour to foster their manufactured exports and diversify their export products. In the meantime, the suspension of the AGOA programme leads to a significant fall in public revenue in the suspended countries, especially for resource-rich countries. The implications of these findings are discussed.
Keywords: F14; O11; H20; 330; African Growth and Opportunity Act (AGOA); Public revenue structure; Export product diversification; Manufactured export performance; Sub-Saharan Africa